Unveil the obvious: the social and educational abyss in pandemic (Olhar de Professor, 2021)
The main aim of this paper is to present the educational scenario and its perspectives, within a neoliberal system and in the midst of a pandemic. First of all, we present the Federative Constitution of Brazil of 1988, a fundamental and supreme law for all Brazilians, which has the objectives to eradicate social inequalities and guarantee education, and how these social and educational inequalities are still present after three decades. Secondly, we present the Brazilian educational context in the face of the pandemic and the vulnerabilities of both students and teachers. We conclude this article by showing that almost nothing has changed in these years since the Constitution, but emphasizing the importance of encouraging and fighting for initiatives, such as the defense of the universalization on internet access in such a current scenario.
Keywords: Social inequality. Education. Sociology of education.